Malaria Infection Effect to Haemoglobin and Haematocrit in Pregnant Mus Musculus - Istiana; Widya Nursantari; Edi Hartoyo; Meitria Syahadatina Noor (Institute of Medico-legal Publications Pvt Ltd, 2022)
Malaria is a disease that is caused by Plasmodium Sp. And infected by Anopheles mosquitos. Kalimantanis one of endemic places for malaria. Prevalence of malaria is 2-76% depent to the places.Effect ofmalaria to pregnant women can be anemia, renal failure, cerebral oedema and death. Prevamence ofanemia because of malaria in pregnant women is about 3-15%. This research was done by using animalmodel to show malaria in pregnant. Goal of this research was to analyze malaria infection effect tohaemoglobin and haematocrit in pregnant Mus musculus. Research design was experimental usingposttest only with control group design. It consisted of K0 for control (20 samples) and K1 for infectedgroup (19 samples).Pregnant Mus musculus was injected P. berghei to infect plasmodium using 0,2 mlinfected serum intraperioteal in the first day of pregnant. Mus musculus was terminated in 19th day ofpregnant and took cardial blood to examine Hb and Ht of pregnant Mus musculus.The result was Hblevel mean for K0= 12,69 gr/dl and K1=12,832 dr/dl. Mean of Ht for K0=38,070% and K1=38,495%.Statistical anayzes used U-Mann Whitney test, with p value for Hb level was 0,574 and Ht was 0,574.The conclusion was malaria infection could not effect yet to Hb dan Ht level in pregnant Mus musculus.